Enhancing Public Engagement of the Deaf or Hard of Hearing Through Media Accessibility in China and Thailand - Liang, Yifan; Satararuji, Kullatip (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
Media accessibility has become a central issue in inclusive communication, yet deaf and hard-of-hearing individuals continue to encounter barriers in education, employment, and public interaction. This study aims to: (1) examine how assistive communication technologies reduce information gaps and promote fair participation; (2) explore how improved accessibility reshapes confidence and Deaf identity; and (3) analyze how policies, schools, families, NGOs, and media organizations collaborate to support long-term barrier-free communication in China and Thailand. A qualitative comparative design was employed. Fifteen in-depth semi-structured interviews were conducted with participants in China (n = 8) and Thailand (n = 7), including deaf and hard-of-hearing individuals as well as hearing professionals engaged in accessibility practice. Interview data were transcribed, iteratively coded using NVivo, and analyzed through cross-country comparison matrices to identify convergences and divergences across institutional and cultural contexts. The findings reveal three interrelated outcomes. First, assistive technologies such as real-time captioning and speech-to-text tools enhance communicative equity, though their effectiveness depends on institutional coordination and cultural integration. Second, accessibility contributes to confidence-building and identity reconstruction by increasing visibility, reducing anxiety, and strengthening Deaf cultural recognition. Third, sustainable inclusion requires multi-actor collaboration across policy systems, educational institutions, families, and media environments. The China–Thailand comparison demonstrates that policy-driven technological diffusion and community-centered cultural participation represent complementary pathways toward routine inclusive communication. This study contributes a comparative inclusive communication model that conceptualizes accessibility as a dynamic ecosystem integrating technology, institutions, and cultural meaning, offering practical implications for inclusive media governance in diverse sociocultural settings.